Factors Affecting Economic Growth in Indonesia - Yulianita, Anna; Ramadhan, Dimas Resy; Mukhlis, Mukhlis (Signifikan: Jurnal Ilmu Ekonomi, 2023)
Inclusive economic growth is an important issue in Indonesia, given the country's uneven economic history and many social and economic inequalities. Despite significant economic progress in recent decades, many Indonesians still live in poverty and are marginalized from economic progress. The data used in this study are panel data from cross-sectional data, namely data from 34 provinces in Indonesia, and time series data, namely data from 2012–2021. The analysis technique used is panel data regression with the fixed effect model method. Based on the results of the study, it is clear that the relationship between poverty, unemployment, and economic inequality is negative and significant for inclusive economic growth in Indonesia. The analysis also emphasizes that efforts to achieve inclusive economic growth should focus on community empowerment, investment in education and training, inclusive infrastructure development, and policies focused on sustainable economic development.JEL Classification: I3, J64, D63, O47How to Cite: Yuanita, A., Ramadhan, D. R, & Mukhlis. (2023). Factors Affecting Economic Growth in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 12(2), 245-262. https://doi.org/10.15408/sjie.v12i2.31186.